PAQR4 promotes the development of hepatocellular carcinoma by activating PI3K/AKT pathway. (30th October 2021) - Zhao, Gang; Shi, Xiaobao; Sun, Zhanbo; Zhao, Pengfei; Lu, Zaiming
Abstract: Progestin and adipoQ receptor 4 (PAQR4) is a novel tumorigenic factor that promotes cell proliferation and metastasis in lung and breast cancer, but its role in hepatocellular carcinoma (HCC) is unknown. The aim of our study was to explore its role and underlying mechanism in the development of HCC. Analysis of GEPIA database indicated that PAQR4 was highly expressed in HCC samples, and the mRNA level of PAQR4 was negatively correlated with the overall survival of HCC patients. Knockdown of PAQR4 in Hep3B cells suppressed cell proliferation by hindering G1/S transition of cell cycle as shown by the flow cytometry analysis. PAQR4 knockdown also expedited the cell apoptosis. Knockdown of PAQR4 repressed the migratory and invasive potential of Hep3B cells. PAQR4 knockdown sensitized Hep3B cells to apatinib-based chemotherapy. PAQR4 knockdown blocked the activation of PI3K/AKT pathway, as reflected by the reduced phosphorylation of AKT and p85. Conversely, overexpression of PAQR4 exerted opposite effects in Huh-7 cells. PI3K inhibitor LY294002 could eliminate the effects of PAQR4 on cell proliferation, apoptosis, chemoresistance, and invasion. In tumor xenograft model, knockdown of PAQR4 suppressed tumor growth in vivo, while PAQR4 overexpression promoted tumor growth. Collectively, our data suggest that PAQR4 has a tumorigenic effect on HCC progression by activating PI3K/AKT pathway.